1998
DOI: 10.1152/ajpheart.1998.274.1.h1
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in cardiac SR Ca2+-release channels during development of heart failure in cardiomyopathic hamsters

Abstract: The cardiomyopathic Syrian hamster develops a progressive cardiomyopathy characterized by cellular necrosis, hypertrophy, cardiac dilatation, and congestive heart failure. This study aimed to identify alterations in cardiac mechanical function and in the cellular content of sarcoplasmic reticulum (SR) Ca2+-release channels (ryanodine receptors, RyR) in the heart of the UM-X7.1 cardiomyopathic hamster during the development of heart failure. Experimental and healthy control hamsters were examined at 8, 18, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…Our choice of this dose and timing of administration of EFO was based on a pilot study in which the results showed that the serum level of EFO significantly increased without producing a significant decrease in blood pressure in the hamsters. Also, according to our previous report, 7 cardiac function in the UM-X7.1 hamster is impaired at the age of 18-20 weeks. The care of the animals and the protocols conformed with the Guiding Principles in the Care and Use of Animals and were in accord with guidelines laid down by the Animal Ethics Committee of Yamaguchi University Graduate School of Medicine.…”
Section: Animalssupporting
confidence: 55%
See 2 more Smart Citations
“…Our choice of this dose and timing of administration of EFO was based on a pilot study in which the results showed that the serum level of EFO significantly increased without producing a significant decrease in blood pressure in the hamsters. Also, according to our previous report, 7 cardiac function in the UM-X7.1 hamster is impaired at the age of 18-20 weeks. The care of the animals and the protocols conformed with the Guiding Principles in the Care and Use of Animals and were in accord with guidelines laid down by the Animal Ethics Committee of Yamaguchi University Graduate School of Medicine.…”
Section: Animalssupporting
confidence: 55%
“…To enable us to determine the left ventricular (LV) dimensions and assess the contractile state in vivo, transthoracic echocardiography was performed as previously described 7 (echocardiograph model SSD-1000, Aloka, Tokyo, Japan, with a 10-MHz sector scan probe). After the echocardiographic examination was completed, the hamsters were given additional pentobarbital sodium (30 mg/kg, im) and the chest was quickly opened.…”
Section: General Protocols and Study Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in the function or content of these proteins have been suggested to contribute to contractile dysfunction in muscle cells during many different disease processes. 31,32 Our data demonstrate that the ryanodine-sensitive channels are depressed in vivo in aortic sections of atherosclerotic plaque in cholesterol-fed rabbits. This depression is particularly evident within and under the plaque area, suggesting that a component associated with the atherogenic environment induces this lesion.…”
Section: Discussionmentioning
confidence: 64%
“…17,18 Briefly, the microsomal fraction that was rich in SR vesicles (0.4 mg/ml) was incubated for 90 min at 37°C in 25 mmol/L imidasole (pH 7. , then removed while under vacuum. After the addition of 5 ml of scintillation fluid, the radioactivity was counted in a scintillation counter (LSC-5100; Aloka, Tokyo, Japan).…”
Section: Assay Of [ 3 H] Ryanodine Bindingmentioning
confidence: 99%